Thrombocytopenia in Pregnancy Induced Hypertension (International Journal of Physiology, 2019)
IntroductionHypertension is a common clinical complication during pregnancy. About 18% of foetal deaths are associated with hypertensive disorders. Out of all the haematological changes that occur in Pregnancy Induced Hypertension (PIH), thrombocytopenia is the most common haematological abnormality found.Material & MethodStudy subjects include 70 women with diagnosed PIH (case) and 70 normotensive pregnant women (control). Platelet count was done.ResultIn PIH cases the low platelet count was seen as compared to normotensive pregnant women. In this study between mean blood pressure & platelet count no correlation was found in normotensive pregnant women but significant negative correlation was found in PIH.ConclusionWe found significant negative correlation between mean blood pressure & platelet count in PIH.